Cover Feature: Comparative Life Cycle Assessment of Chemical and Biocatalytic 2'3'‐Cyclic GMP‐AMP Synthesis (ChemSusChem 5/2023). Issue 5 (22nd February 2023) - Becker, Martin; Ziemińska‐Stolarska, Aleksandra; Markowska, Dorota; Lütz, Stephan; Rosenthal, Katrin
Abstract : The Cover Feature shows shows the comparison of biocatalytic and chemical synthesis routes for cyclic dinucleotides based on life cycle assessment. It was shown that biocatalytic synthesis is superior to chemical synthesis by at least one magnitude in all categories considered. More information can be found in the Research Article by M. Becker et al .